Crystal structure of 1-(p-tolylphenyl)-4-(2-thienoyl)-3-methyl-1H-pyrazol-5-ol, C16H14N2O2S - Jin Tong-Yin; Yang Jia-Ning; Chen Hong-Li; Zhang Heng-Qiang; Liao Lian-Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C16H14N2O2S, orthorhombic, Pca21 (no. 29), a = 11.5382(5) Å, b = 8.2480(5) Å, c = 15.1726(11) Å, V = 1,443.94(15) Å3, Z = 4, Rgt (F) = 0.0379, wRref (F 2) = 0.0990, T = 173 K.